Beyond NAMs versus animal models: Context of use as the governing framework for integrated nonclinical strategies in drug development - Stefano Gaburro; Brian Berridge; Nicholas W. Kelley; Eckhard von Keutz; Marc Ferrer; Clive Roper; Michael J. Fossler; Jeffrey J. Bajramovic; Jean-Pierre Valentin; Timothy McGovern; Todd Bourcier; Ronald L. Wange; et al. (Regulatory Toxicology and Pharmacology, 2026)

Assessing uncertainty in conservation practice performance: effect of sample frequency on bioreactor nitrate removal - Mark R. Williams; Laura E. Christianson; Kevin W. King; Reid D. Christianson; Jason Roth; Gary W. Feyereisen (Environmental Monitoring and Assessment, 2026)

Water volumes, heat flow, and solute discharge from Old Faithful Geyser eruptions, Yellowstone National Park, USA - Shaul Hurwitz; R. Blaine McCleskey; Maxwell L. Rudolph; Sara Peek; David A. Roth; Melissa Schott-Atkins; Michael Manga; Kiernan F. Folz Donahue; Mara H. Reed; Jefferson D.G. Hungerford (Journal of Volcanology and Geothermal Research, 2026)

Decadal migration timing and temporal variation in dive behavior of an endangered beluga whale population - Kasey P. Ryan; Sean F. Ryan; Mads Peter Heide-Jørgensen; Steven H. Ferguson; Sasha R. X. Dall; James D. Roth; Cortney A. Watt (Frontiers in Marine Science, 2026)
Introduction Understanding migration timing and movement behavior is critical for predicting population responses to environmental changes. The beluga whale ( Delphinapterus leucas ) population in Cumberland Sound, Nunavut, is currently endangered due to historical and ongoing overharvesting. Methods By comparing satellite telemetry data from two distinct time periods (1998–1999 and 2006–2008), we evaluated beluga whale dive behavior and migration timing in relation to environmental and seasonal factors. To infer potential prey shifts, we compared the proportion of dives deeper than 100 m, where Arctic cod ( Boreogadus saida ) are typically found, with shallower dives indicative of capelin ( Mallotus villosus ) foraging. Dive behavior was analyzed in relation to seasonal progression (day of year), time period, ice cover, bottom depth, and sex using mixed-effects models. Migration timing was evaluated using latitudinal thresholds and a transect line to identify the timing and variability of southward autumn movements relative to sea ice formation. Results We found significant seasonal (day of year) variation in dive behavior, with deep dives increasing from September to December. Additionally, there was a notable shift to more shallow dives in the second time period compared to the first, suggesting a change in foraging from Arctic cod to capelin. We found that the whales’ initial movements out of their summering area appeared largely independent of ice phenology, while their movements later in their migration were highly variable. Discussion The shift in prey likely occurred due to changes in prey distribution driven by warmer ocean temperatures, which may have negative long-term impacts on population health. Some of these behavioral trends contrasted with those of other beluga whale populations, emphasizing the need for population-specific management strategies to support long-term survival of the Cumberland Sound beluga whale population.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

Cue relevance during navigation is a function of scale and experience - Aaron R. Krochmal; Timothy C. Roth; Nathaniel T. Simmons (Animal Behaviour, 2025)

Development of diagnostic markers for the disease susceptibility gene Tsn1 in wheat reveals novel resistance alleles and a new locus required for ToxA sensitivity - Katherine L. D. Running; Krishna Acharya; Tiana M. Roth; Gurminder Singh; Agnes Szabo-Hever; Amanda R. Peters Haugrud; Jason D. Fiedler; Timothy L. Friesen; Justin D. Faris (Theoretical and Applied Genetics, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Holocene rock varnish microstratigraphy in the Dead Sea basin and Negev Desert: Chronometric application and climatic implication - Tanzhuo Liu; Wallace S. Broecker; Sidney R. Hemming; Helena Roth; Zachary C. Dunseth; Guy D. Stiebel; Mordechai Stein (Quaternary Science Reviews, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Genome-scale metabolic model accurately predicts fermentation of glucose by Chromochloris zofingiensis - Michelle Meagher; Alex Metcalf; Mark Vigliotti; S. Alex Ramsey; Walter Prentice; Luca Cohen; Shivani Upadhyaya; Melissa S. Roth; Nanette R. Boyle (Algal Research, 2024)

Exploring weight-related self-monitoring as a potential risk factor for eating disorder symptoms in adults – A systematic review and meta-analysis - Annika M. Roth; Judith R. Gruber; Andreas Reif; Martin Schultze; Silke Matura (Appetite, 2024)

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Evaluating strategies to increase PET bottle recycling in the United States - R. Basuhi; Karan Bhuwalka; Richard Roth; Elsa A. Olivetti (Journal of Industrial Ecology, 2024)
In the United States, polyethylene terephthalate (PET) bottle collection rates have not increased in a decade. Recycling rates remain abysmal while industry commitments and policy targets escalate the demand for recycled plastics. We investigate the PET bottle recycling system, where collection is a critical bottleneck and recycled PET supply is not meeting the expected demand. We characterize demand for recycled PET (R‐PET), analyze scenarios of expanding deposit return systems (DRS), and quantify cost barriers to improving PET bottle recycling. We find that a nation‐wide DRS can increase PET bottle recycling rates from 24% to 82%, supplying approximately 2700 kt of recycled PET annually. With stability in demand, we estimate that this PET bottle recycling system can achieve 65% bottle‐to‐bottle circularity, at a net cost of 360 USD/tonne of PET recycled. We also discuss environmental impacts, stakeholder implications, producer responsibility, and complimentary policies toward an efficient and effective recycling system.

Factors influencing detection of invasive Red Swamp Crayfish Procambarus clarkii (Girard, 1852) in Michigan ponds - William R. Budnick; Dan Hayes; Seth Herbst; Jeannette Kanefsky; Lucas Nathan; Brian M. Roth; Nicholas M. Sard; Kim T. Scribner; Kelley Smith; Sara Thomas (Hydrobiologia, 2024)

Trophic Structure and a Temporal Shift in Trophic Diversity of Mobile Consumers in a Subarctic Estuary - Jillian R. St. George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuaries and Coasts, 2024)
Quantifying trophic relationships within and between species in terms of trophic position, ontogeny and trophic diversity provides information on community-level structure and function. Little attention has been focused on examining the trophic structure and temporal changes of communities in freshwater-marine coupled systems in the subarctic and associated impacts of anthropogenic activity on trophic interactions. Therefore, the objective of this study was to quantify the trophic position of mobile consumers (15 species in total) within the lower Churchill River area (Churchill, Manitoba, Canada), examine trophic position variation in relation to ontogeny, and measure the trophic diversity of a fish assemblage before (1993–1995) and after (2019–2020) the installation of the Churchill River weir in the late 1990s. We used stable isotopes (δ 13 C and δ 15 N) to quantify individual and group-level variation in trophic position of thirteen fish species and two seal species and also assessed six community-level metrics of a three fish species assemblage between time periods. Overall, species that mainly foraged on freshwater resources occupied lower trophic positions than species that mainly consumed marine resources. Trophic position increased with fish age only in cisco, fourhorn sculpin, Greenland cod and northern pike. A temporal shift from a trophically diverse to a more trophically redundant fish assemblage occurred between 1993–1995 and 2019–2020. As a result, these predator species now play similar trophic roles. Information on the long-term change in trophic structure of this sub-Arctic estuarine system may help with understanding how anthropogenic activity and climate change have influenced the trophic diversity of a fish assemblage inhabiting this system.

3D Monte-Carlo simulation of Ganymede’s atmosphere - Audrey Vorburger; Shahab Fatemi; Shane R. Carberry Mogan; André Galli; Lucas Liuzzo; Andrew R. Poppe; Lorenz Roth; Peter Wurz (Icarus, 2024)

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

Editorial: Syngnathid fishes: biology, ecology, physiology, conservation and innovative rearing techniques - Miquel Planas; Michele Gristina; Jorge Palma; Geng Qin; Emily Rose; Olivia Roth; Peter R. Teske (Frontiers in Marine Science, 2023)

Effect of erythrophagocytosis-induced ferroptosis during angiogenesis in atherosclerotic plaques - Pauline Puylaert; Lynn Roth; Melissa Van Praet; Isabel Pintelon; Catalina Dumitrascu; Alexander van Nuijs; Greta Klejborowska; Pieter-Jan Guns; Tom Vanden Berghe; Koen Augustyns; Guido R. Y. De Meyer; Wim Martinet (Angiogenesis, 2023)
Intraplaque (IP) angiogenesis is a key feature of advanced atherosclerotic plaques. Because IP vessels are fragile and leaky, erythrocytes are released and phagocytosed by macrophages (erythrophagocytosis), which leads to high intracellular iron content, lipid peroxidation and cell death. In vitro experiments showed that erythrophagocytosis by macrophages induced non-canonical ferroptosis, an emerging type of regulated necrosis that may contribute to plaque destabilization. Erythrophagocytosis-induced ferroptosis was accompanied by increased expression of heme-oxygenase 1 and ferritin, and could be blocked by co-treatment with third generation ferroptosis inhibitor UAMC-3203. Both heme-oxygenase 1 and ferritin were also expressed in erythrocyte-rich regions of carotid plaques from ApoE −/− Fbn1 C1039G+/− mice, a model of advanced atherosclerosis with IP angiogenesis. The effect of UAMC-3203 (12.35 mg/kg/day) on atherosclerosis was evaluated in ApoE −/− Fbn1 C1039G+/− mice fed a western-type diet (WD) for 12 weeks (n = 13 mice/group) or 20 weeks (n = 16–21 mice/group) to distinguish between plaques without and with established IP angiogenesis, respectively. A significant decrease in carotid plaque thickness was observed after 20 weeks WD (87 ± 19 μm vs. 166 ± 20 μm, p = 0.006), particularly in plaques with confirmed IP angiogenesis or hemorrhage (108 ± 35 μm vs. 322 ± 40 μm, p = 0.004). This effect was accompanied by decreased IP heme-oxygenase 1 and ferritin expression. UAMC-3203 did not affect carotid plaques after 12 weeks WD or plaques in the aorta, which typically do not develop IP angiogenesis. Altogether, erythrophagocytosis-induced ferroptosis during IP angiogenesis leads to larger atherosclerotic plaques, an effect that can be prevented by ferroptosis inhibitor UAMC-3203.

Habitat coupling dynamics of mobile consumers along a freshwater and marine resource gradient in a sub-Arctic estuarine system - Jillian R. St George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuarine, Coastal and Shelf Science, 2023)

Distinct fungal and bacterial responses to fire severity and soil depth across a ten-year wildfire chronosequence in beetle-killed lodgepole pine forests - Marcos V. Caiafa; Amelia R. Nelson; Thomas Borch; Holly K. Roth; Timothy S. Fegel; Charles C. Rhoades; Michael J. Wilkins; Sydney I. Glassman (Forest Ecology and Management, 2023)

Ganymede's atmosphere as constrained by HST/STIS observations - F. Leblanc; L. Roth; J.Y. Chaufray; R. Modolo; M. Galand; N. Ivchenko; G. Carnielli; C. Baskevitch; A. Oza; A.L.E. Werner (Icarus, 2023)

The role of circulating cell-free DNA as an inflammatory mediator after stroke - Stefan Roth; Saskia R. Wernsdorf; Arthur Liesz (Seminars in Immunopathology, 2023)
Stroke is the second leading cause of death worldwide and a leading cause of disability. Clinical and experimental studies highlighted the complex role of the immune system in the pathophysiology of stroke. Ischemic brain injury leads to the release of cell-free DNA, a damage-associated molecular pattern, which binds to pattern recognition receptors on immune cells such as toll-like receptors and cytosolic inflammasome sensors. The downstream signaling cascade then induces a rapid inflammatory response. In this review, we are highlighting the characteristics of cell-free DNA and how these can affect a local as well as a systemic response after stroke. For this purpose, we screened literature on clinical studies investigating cell-free DNA concentration and properties after brain ischemia. We report the current understanding for mechanisms of DNA uptake and sensing in the context of post-stroke inflammation. Moreover, we compare possible treatment options targeting cell-free DNA, DNA-sensing pathways, and the downstream mediators. Finally, we describe clinical implications of this inflammatory pathway for stroke patients, open questions, and potential future research directions.

The case for investigating the cognitive map in nonavian reptiles - Aaron R. Krochmal; Timothy C. Roth (Animal Behaviour, 2023)

Multiple sources implicated in the red swamp crayfish invasion in Michigan, USA - N. M. Sard; K. R. Smith; B. M. Roth; L. R. Nathan; S. J. Herbst; K. T. Scribner (Biological Invasions, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Dive characteristics of Cross Seamount beaked whales from long‐term passive acoustic monitoring at the Pacific Missile Range Facility, Kauaʻi - Roanne Manzano‐Roth; E. Elizabeth Henderson; Gabriela C. Alongi; Cameron R. Martin; Stephen W. Martin; Brian Matsuyama (Marine Mammal Science, 2023)
Beaked whale foraging pulses were detected on the Pacific Missile Range Facility (PMRF) off Kauaʻi, Hawaiʻi, via long term passive acoustic monitoring. The unidentified pulses do not match foraging pulses of known species on the range but are similar to the unidentified beaked whale first detected at Cross Seamount, Hawaiʻi. Although there has not been a visual confirmation of the unidentified beaked whale species, analysis of data collected from 2007 to 2019 has identified beaked whale foraging dive characteristics from echolocation pulses. From the 13 years of data, the most distinct patterns were that all foraging dives occurred at night and the nighttime foraging dive rate was 0.11 group vocal periods (GVP) per hour, with most detections on shallow hydrophones (625–1,000 m deep) over steep bathymetric slopes. Data collected during U.S. Navy training events were used to compare dive behavior during mid‐frequency active sonar (MFAS) activity against baseline periods; it was determined that the whales reduced GVPs during sonar and these remained low for at least 3 days after the training events. These results are the first long‐term record of acoustic signals from the Cross Seamount beaked whale and provide important insights into their habitat use and occurrence patterns.

Gaining Insights about Forest Health Prescriptions from Loggers and Foresters: Understudied Voices in the Human Dimensions of Forest Health - Stephanie A. Snyder; Charles R. Blinn; Sarah Roth; Marcella Windmuller-Campione (Environmental Management, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Measuring circulating triglycerides in free-living birds: evaluation of a field-usable point-of-care analyzer for American woodcock - Christopher M. Roelandt; Amber M. Roth; Scott R. McWilliams; Jill C. Witt (Journal of Ornithology, 2022)

The role of oxygen in stimulating methane production in wetlands - Jared L. Wilmoth; Jeffra K. Schaefer; Danielle R. Schlesinger; Spencer W. Roth; Patrick G. Hatcher; Julie K. Shoemaker; Xinning Zhang (Global Change Biology, 2021)
Methane (CH 4 ), a potent greenhouse gas, is the second most important greenhouse gas contributor to climate change after carbon dioxide (CO 2 ). The biological emissions of CH 4 from wetlands are a major uncertainty in CH 4 budgets. Microbial methanogenesis by Archaea is an anaerobic process accounting for most biological CH 4 production in nature, yet recent observations indicate that large emissions can originate from oxygenated or frequently oxygenated wetland soil layers. To determine how oxygen (O 2 ) can stimulate CH 4 emissions, we used incubations of Sphagnum peat to demonstrate that the temporary exposure of peat to O 2 can increase CH 4 yields up to 2000‐fold during subsequent anoxic conditions relative to peat without O 2 exposure. Geochemical (including ion cyclotron resonance mass spectrometry, X‐ray absorbance spectroscopy) and microbiome (16S rDNA amplicons, metagenomics) analyses of peat showed that higher CH 4 yields of redox‐oscillated peat were due to functional shifts in the peat microbiome arising during redox oscillation that enhanced peat carbon (C) degradation. Novosphingobium species with O 2 ‐dependent aromatic oxygenase genes increased greatly in relative abundance during the oxygenation period in redox‐oscillated peat compared to anoxic controls. Acidobacteria species were particularly important for anaerobic processing of peat C, including in the production of methanogenic substrates H 2 and CO 2 . Higher CO 2 production during the anoxic phase of redox‐oscillated peat stimulated hydrogenotrophic CH 4 production by Methanobacterium species. The persistence of reduced iron (Fe(II)) during prolonged oxygenation in redox‐oscillated peat may further enhance C degradation through abiotic mechanisms (e.g., Fenton reactions). The results indicate that specific functional shifts in the peat microbiome underlie O 2 enhancement of CH 4 production in acidic, Sphagnum ‐rich wetland soils. They also imply that understanding microbial dynamics spanning temporal and spatial redox transitions in peatlands is critical for constraining CH 4 budgets; predicting feedbacks between climate change, hydrologic variability, and wetland CH 4 emissions; and guiding wetland C management strategies.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

High summer temperatures amplify functional differences between coral‐ and algae‐dominated reef communities - Florian Roth; Nils RAdecker; Susana Carvalho; Carlos M. Duarte; Vincent Saderne; Andrea Anton; Luis Silva; Maria Ll. Calleja; XosÉ Anxelu G. MorÁn; Christian R. Voolstra; Benjamin Kürten; Burton H. Jones; et al. (Ecology, 2021)
Shifts from coral to algal dominance are expected to increase in tropical coral reefs as a result of anthropogenic disturbances. The consequences for key ecosystem functions such as primary productivity, calcification, and nutrient recycling are poorly understood, particularly under changing environmental conditions. We used a novel in situ incubation approach to compare functions of coral‐ and algae‐dominated communities in the central Red Sea bimonthly over an entire year. In situ gross and net community primary productivity, calcification, dissolved organic carbon fluxes, dissolved inorganic nitrogen fluxes, and their respective activation energies were quantified to describe the effects of seasonal changes. Overall, coral‐dominated communities exhibited 30% lower net productivity and 10 times higher calcification than algae‐dominated communities. Estimated activation energies indicated a higher thermal sensitivity of coral‐dominated communities. In these communities, net productivity and calcification were negatively correlated with temperature (>40% and >65% reduction, respectively, with +5°C increase from winter to summer), whereas carbon losses via respiration and dissolved organic carbon release more than doubled at higher temperatures. In contrast, algae‐dominated communities doubled net productivity in summer, while calcification and dissolved organic carbon fluxes were unaffected. These results suggest pronounced changes in community functioning associated with coral‐algal phase shifts. Algae‐dominated communities may outcompete coral‐dominated communities because of their higher productivity and carbon retention to support fast biomass accumulation while compromising the formation of important reef framework structures. Higher temperatures likely amplify these functional differences, indicating a high vulnerability of ecosystem functions of coral‐dominated communities to temperatures even below coral bleaching thresholds. Our results suggest that ocean warming may not only cause but also amplify coral–algal phase shifts in coral reefs.

Simultaneous Measurements of Dinitrogen Fixation and Denitrification Associated With Coral Reef Substrates: Advantages and Limitations of a Combined Acetylene Assay - Yusuf C. El-Khaled; Florian Roth; Nils Rädecker; Najeh Kharbatia; Burton H. Jones; Christian R. Voolstra; Christian Wild (Frontiers in Marine Science, 2020)

Ecophysiology of mesophotic reef‐building corals in Hawai‘i is influenced by symbiont–host associations, photoacclimatization, trophic plasticity, and adaptation - Jacqueline L. Padilla‐Gamiño; Melissa S. Roth; Lisa J. Rodrigues; Christina J. Bradley; Robert R. Bidigare; Ruth D. Gates; Celia M. Smith; Heather L. Spalding (Limnology and Oceanography, 2019)
Mesophotic reef corals remain largely unexplored in terms of the genetic adaptations and physiological mechanisms to acquire, allocate, and use energy for survival and reproduction. In the Hawaiian Archipelago, the Leptoseris species complex form the most spatially extensive mesophotic coral ecosystem known and provide habitat for a unique community. To study how the ecophysiology of Leptoseris species relates to symbiont–host specialization and understand the mechanisms responsible for coral energy acquisition in extreme low light environments, we examined Symbiodinium (endosymbiotic dinoflagellate) photobiological characteristics and the lipids and isotopic signatures from Symbiodinium and coral hosts over a depth‐dependent light gradient (55–7 μ mol photons m −2 s −1 , 60–132 m). Clear performance differences demonstrate different photoadaptation and photoacclimatization across this genus. Our results also show that flexibility in photoacclimatization depends primarily on Symbiodinium type. Colonies harboring Symbiodinium sp. COI‐2 showed significant increases in photosynthetic pigment content with increasing depth, whereas colonies harboring Symbiodinium spp. COI‐1 and COI‐3 showed variability in pigment composition, yield measurements for photosystem II, as well as size and density of Symbiodinium cells. Despite remarkable differences in photosynthetic adaptive strategies, there were no significant differences among lipids of Leptoseris species with depth. Finally, isotopic signatures of both host and Symbiodinium changed with depth, indicating that coral colonies acquired energy from different sources depending on depth. This study highlights the complexity in physiological adaptations within this symbiosis and the different strategies used by closely related mesophotic species to diversify energy acquisition and to successfully establish and compete in extreme light‐limited environments.

Constraints to the capacity of smallholder farming households to adapt to climate change in South and Southeast Asia - Peter R. Brown; Sharmin Afroz; Lytoua Chialue; T. Chiranjeevi; Sotheary El; Clemens M. Grünbühel; Iqbal Khan; Cathy Pitkin; V. Ratna Reddy; Christian H. Roth; Silinthone Sacklokham; Liana J. Williams (Climate and Development, 2019)

Changes in the distribution of Michigan crayfishes and the influence of invasive rusty crayfish (Faxonius rusticus) on native crayfish substrate associations - Kelley R. Smith; Brian M. Roth; Michael L. Jones; Daniel B. Hayes; Seth J. Herbst; Nicholas Popoff (Biological Invasions, 2019)

A Prospective Study of Humoral and Cellular Immune Responses to Hepatitis B Vaccination in Habitual Marijuana Smokers - Sylvia M. Kiertscher; Pallavi R. Gangalum; Grace Ibrahim; Donald P. Tashkin; Michael D. Roth (Journal of Neuroimmune Pharmacology, 2018)

Integration of sudden death syndrome resistance loci in the soybean genome - Hao-Xun Chang; Mitchell G. Roth; Dechun Wang; Silvia R. Cianzio; David A. Lightfoot; Glen L. Hartman; Martin I. Chilvers (Theoretical and Applied Genetics, 2018)

Influence of browsing damage and overstory cover on regeneration of American beech and sugar maple nine years following understory herbicide release in central Maine - Arun K. Bose; Robert G. Wagner; Brian E. Roth; Aaron R. Weiskittel (New Forests, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

The effects of warming and ocean acidification on growth, photosynthesis, and bacterial communities for the marine invasive macroalga Caulerpa taxifolia - Alexandra J. Roth‐Schulze; Torsten Thomas; Peter Steinberg; Marty R. Deveney; Jason E. Tanner; Kathryn H. Wiltshire; Stephanie Papantoniou; John W. Runcie; C. Frederico D. Gurgel (Limnology and Oceanography, 2018)
Caulerpa taxifolia is a pantropical green benthic marine macroalga, and one of the best known marine invasive species in temperate coastal habitats. In Australia, this species has been introduced to seven estuaries along New South Wales and one in South Australia. How this alga will perform under future climate change scenarios is however not well defined. This study experimentally assessed the effects of ocean acidification and global warming on the growth, photosynthetic performance and the bacterial community on two populations of C. taxifolia , one native and one invasive. A range of complex significant interactive effects between pH, temperature, and initial plant size on the growth of C. taxifolia were observed, but no effect of population origin and photosystem II (PSII) fluorescence quantum yield parameters were detected. No significant effects of the treatment combinations were observed on bacterial community richness or diversity. Only one bacterial species out of 1087 present on the algae showed significant changes between pH treatments at high temperature (24°C). This bacterium belonged to the genus Planctomyces and its relative abundance was more than 10 times higher in samples with low pH compared to the control. Higher plant growth was observed under all higher pCO 2 and lower pH conditions suggesting that C. taxifolia will benefit from climate change, posing a potential higher risk in invaded locations.

Household types as a tool to understand adaptive capacity: case studies from Cambodia, Lao PDR, Bangladesh and India - Liana J. Williams; Sharmin Afroz; Peter R. Brown; Lytoua Chialue; Clemens M. Grünbühel; Tanya Jakimow; Iqbal Khan; Mao Minea; V. Ratna Reddy; Silinthone Sacklokham; Emmanuel Santoyo Rio; Mak Soeun; et al. (Climate and Development, 2016)

Increased blubber cortisol in ice-entrapped beluga whales (Delphinapterus leucas) - Marci R. Trana; James D. Roth; Gregg T. Tomy; W. Gary Anderson; Steven H. Ferguson (Polar Biology, 2016)

Assessing vulnerability: an integrated approach for mapping adaptive capacity, sensitivity, and exposure - Shawn W. Margles Weis; Vera N. Agostini; Lynnette M. Roth; Ben Gilmer; Steven R. Schill; John English Knowles; Ruth Blyther (Climatic Change, 2016)

Effect of manganese treatment on the accumulation on biologically relevant metals in rat cochlea and brain by inductively coupled plasma mass spectrometry - Elizabeth J. Mullin; Stacia R. Wegst-Uhrich; Dalian Ding; Senthilvelan Manohar; Vijaya Prakash Krishnan Muthaiah; Richard Salvi; Diana S. Aga; Jerome A. Roth (BioMetals, 2015)

Increased frequency of JC-polyomavirus detection in rheumatoid arthritis patients treated with multiple biologics - Jens Verheyen; Kseniya Maizus; Eugen Feist; Zebulon Tolman; Elena Knops; Jasemine Saech; Lydia Spengler; Tim Waterboer; Gerd R. Burmester; Michael Pawlita; Herbert Pfister; Andrea Rubbert-Roth (Medical Microbiology and Immunology, 2015)

Carry-over effects and foraging ground dynamics of a major loggerhead breeding aggregation - Simona A. Ceriani; James D. Roth; Anton D. Tucker; Daniel R. Evans; David S. Addison; Christopher R. Sasso; Llewellyn M. Ehrhart; John F. Weishampel (Marine Biology, 2015)

Sustainability of Corn Stover Harvest Strategies in Pennsylvania - Paul R. Adler; Benjamin M. Rau; Gregory W. Roth (BioEnergy Research, 2015)

A whole-lake experiment to control invasive rainbow smelt (Actinoperygii, Osmeridae) via overharvest and a food web manipulation - Jereme W. Gaeta; Thomas R. Hrabik; Greg G. Sass; Brian M. Roth; Stephen J. Gilbert; M. Jake Vander Zanden (Hydrobiologia, 2015)

Species richness and areas of endemism of oryzomyine rodents (Cricetidae, Sigmodontinae) in South America: an ndm / vndm approach - Joyce R. do Prado; Pamella G. G. Brennand; Leandro P. Godoy; Gustavo S. Libardi; Edson F. de Abreu‐Júnior; Paulo R. O. Roth; Elisandra A. Chiquito; Alexandre R. Percequillo (Journal of Biogeography, 2015)
Aim To infer areas of endemism for the tribe Oryzomyini in South America by employing a database of species richness and geographical distribution, and to compare these results with areas of endemism and species richness proposed in the literature for other taxa. Location We analysed specimens of the tribe Oryzomyini distributed throughout South and Central America, which are housed in European, North and South American museums and collections. Methods We analysed 2768 occurrence records for 102 species of the tribe Oryzomyini using the ndm / vndm algorithm and three different grid sizes to assess the possible effects of grid cell area on the results. Results Using the overlap of consensus areas in South America, we identified three generalized areas of endemism for the Oryzomyini: north‐western South America ( NWSA ), eastern South American ( ESA ), and northern South America ( NSA ); we also identified the Galápagos archipelago ( GA ) as an area of endemism. Main conclusions Areas of endemism detected in the continental portion of South America include its three main mountain chains: the Andes Cordillera, the Guyanan Shields, and an area east of the Brazilian Shield named Serra do Mar. Each of these regions encompasses many different types of vegetation, and the species richness and composition of the areas of endemism of the tribe are directly related to this environmental diversity. Different grid sizes affected the distributional heterogeneity of the consensus areas. The smallest grid cell size identified mainly Andean areas, which contain a higher number of more exclusive species in a small area along a steep elevational gradient. In contrast, the largest grid size identified areas of endemism along an environmental gradient that co‐varied with latitude and longitude. The identified areas of endemism are corroborated by previous studies on other taxa.

Endogenous concentrations of biologically relevant metals in rat brain and cochlea determined by inductively coupled plasma mass spectrometry - Stacia R. Wegst-Uhrich; Elizabeth J. Mullin; Dalian Ding; Senthilvelan Manohar; Richard Salvi; Diana S. Aga; Jerome A. Roth (BioMetals, 2015)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

Assessment of Juvenile Pigs to Serve as Human Pediatric Surrogates for Preclinical Formulation Pharmacokinetic Testing - Wyatt J. Roth; Candice B. Kissinger; Robyn R. McCain; Bruce R. Cooper; Jeremy N. Marchant-Forde; Rachel C. Vreeman; Sophia Hannou; Gregory T. Knipp (The AAPS Journal, 2013)

Are all eggs created equal? A case study from the Hawaiian reef-building coral Montipora capitata - Jacqueline L. Padilla-Gamiño; Robert R. Bidigare; Daniel J. Barshis; Ada Alamaru; Laetitia Hédouin; Xavier Hernández-Pech; Frederique Kandel; Sherril Leon Soon; Melissa S. Roth; Lisa J. Rodrigues; Andrea G. Grottoli; Claudia Portocarrero; et al. (Coral Reefs, 2013)

Differential hippocampal gene expression is associated with climate‐related natural variation in memory and the hippocampus in food‐caching chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; R. Kramer; F. Schilkey; A. M. van der Linden (Molecular Ecology, 2013)
There is significant and often heritable variation in cognition and its underlying neural mechanisms, yet specific genetic contributions to such variation are not well characterized. Black‐capped chickadees present a good model to investigate the genetic basis of cognition because they exhibit tremendous climate‐related variation in memory, hippocampal morphology and neurogenesis rates throughout the North American continent, and these cognitive traits appear to have a heritable basis. We examined the hippocampal transcriptome profiles of laboratory‐reared chickadees from the two most divergent populations to test whether differential gene expression in the hippocampus is associated with population differences in spatial memory, hippocampal morphology and adult hippocampal neurogenesis rates. Using high‐resolution mRNA sequencing coupled to a de novo transcriptome assembly, we generated 23 295 consensus sequences, which predicted 16 206 protein sequences with 13 982 showing high similarity to known protein sequences or conserved hypothetical proteins in other species. Of these, we identified differential expression in nearly 380 genes, with 47 genes specifically linked to neurogenesis, apoptosis, synaptic function, and learning and memory processes. Many of the other differentially expressed genes, however, may be associated with other functions. Our study presents the first avian hippocampal transcriptome, and it is the first study identifying differential gene expression associated with natural variation in cognition and the hippocampus. Our results provide additional support to the hypothesis that population differences in memory, hippocampal morphology and neurogenesis in chickadees have likely resulted from natural selection that appears to act on memory and its underlying neural mechanisms.

Selected Trace Elements in the Sacramento River, California: Occurrence and Distribution - H. E. Taylor; R. C. Antweiler; D. A. Roth; C. N. Alpers; P. Dileanis (Archives of Environmental Contamination and Toxicology, 2012)

Live chilling of Atlantic salmon: physiological response to handling and temperature decrease on welfare - A. Foss; E. Grimsbø; E. Vikingstad; R. Nortvedt; E. Slinde; B. Roth (Fish Physiology and Biochemistry, 2012)

Autistic Traits Below the Clinical Threshold: Re-examining the Broader Autism Phenotype in the 21st Century - E. Sucksmith; I. Roth; R. A. Hoekstra (Neuropsychology Review, 2011)

Protein Kinase B (Akt) and Mitogen-Activated Protein Kinase p38α in Retinal Ischemic Post-Conditioning - John C. Dreixler; Ajay Sampat; Afzhal R. Shaikh; Michael Alexander; Marcus M. Marcet; Steven Roth (Journal of Molecular Neuroscience, 2011)

ICUC‐7 Urban Climate Special Issue - M. Roth; R. Emmanuel; T. Ichinose; J. Salmond (International Journal of Climatology, 2011)

A simulation of food‐web interactions leading to rainbow smelt Osmerus mordax dominance in Sparkling Lake, Wisconsin - B. M. Roth; T. R. Hrabik; C. T. Solomon; N. Mercado‐Silva; J. F. Kitchell (Journal of Fish Biology, 2010)
A process‐based simulation model was used to examine the nature and intensity of food‐web interactions that allow Osmerus mordax to dominate invaded lakes. The model simulates food‐web interactions among linked populations of O. mordax , Coregonus artedi and Sander vitreus . Simulations indicated that O. mordax dominate where: (1) adult O. mordax prey on young‐of‐the‐year (YOY) C. artedi , (2) YOY O. mordax negatively affect YOY S. vitreus through competition and (3) adult S. vitreus experience moderate fishing mortality. Osmerus mordax dominated simulations across a broad range of variable values that regulated competition and predation, and displayed threshold responses to increasing angler harvest. Consequently, angler harvest should be carefully managed in lakes susceptible to O. mordax invasions because the alternative could lead to fishery collapse.

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Age‐specific reproduction and survival of individually marked Wood Thrushes, Hylocichla mustelina - William P. Brown; Roland R. Roth (Ecology, 2009)
Several nonexclusive, sometimes contradictory, hypotheses have been employed to explain age‐related changes in reproduction and survival among vertebrates. We evaluated these hypotheses with observations collected from a 31‐year study of individually marked Wood Thrushes ( Hylocichla mustelina ). Age‐specific fledgling production, survival probabilities, and derived life table columns are presented here. Additionally, we report “genetic value,” or the number of young remaining to be recruited into the breeding population by individuals of age x . Controlling for age of mate, the presence of some individuals in multiple years, and the effect of year of breeding, reproduction and survival peaked in middle‐aged birds of each sex and declined later in life for the oldest individuals. We could not exclude the selection hypothesis (removal of inferior individuals) as an explanation for improved female reproduction until middle age. The age at last reproduction was a significant determinant of age‐related reproductive success, indicating a disappearance of low‐quality individuals. Yearling females that did not successfully reproduce had greater within‐season emigration than all other age classes of each sex, regardless of the reproductive success of other classes. For males, we favored the constraint hypothesis (improved reproduction with experience) to explain greater reproductive output with increasing age until at least middle age. For each sex, the age of the mate independently influenced all measures of reproductive performance, but there was generally a linear or quadratic, rather than interactive, effect of the mate's age on reproduction. For both sexes, hypotheses of age‐related reproduction were only partially supported because of effects of senescence, or a decline in reproductive output or survival probabilities with increasing age. Senescence may confound attempts to examine or apply general hypotheses of age‐related reproduction that assume a monotonic relationship between age and reproduction or survival.

Trial-to-trial size variability of motor-evoked potentials. A study using the triple stimulation technique - Kai M. Rösler; Denise M. Roth; Michel R. Magistris (Experimental Brain Research, 2008)

Mercury and Organic Carbon Dynamics During Runoff Episodes from a Northeastern USA Watershed - P. F. Schuster; J. B. Shanley; M. Marvin-Dipasquale; M. M. Reddy; G. R. Aiken; D. A. Roth; H. E. Taylor; D. P. Krabbenhoft; J. F. DeWild (Water, Air, & Soil Pollution, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

WAY-100635 is a potent dopamine D4 receptor agonist - Benjamin R. Chemel; Bryan L. Roth; Blaine Armbruster; Val J. Watts; David E. Nichols (Psychopharmacology, 2006)

Ultrastructure of the membrane systems in the unicellular cyanobacterium Synechocystis sp. strain PCC 6803 - Michelle Liberton; R. Howard Berg; John Heuser; Robin Roth; Himadri B. Pakrasi (Protoplasma, 2006)

Effect of In Vivo Administration of Ethylmalonic Acid on Energy Metabolism in Rat Tissues - Gustavo da C. Ferreira; Karina Roth André; Patrícia Fernanda Schuck; Carolina M. Viegas; Anelise Tonin; Daniella de Moura Coelho; Angela T. S. Wyse; Clóvis M. D. Wannmacher; Carmen R. Vargas; Moacir Wajner (Metabolic Brain Disease, 2006)

Temporal dynamics of CO2 fluxes and profiles over a Central European city - R. Vogt; A. Christen; M. W. Rotach; M. Roth; A. N. V. Satyanarayana (Theoretical and Applied Climatology, 2006)

BUBBLE – an Urban Boundary Layer Meteorology Project - M. W. Rotach; R. Vogt; C. Bernhofer; E. Batchvarova; A. Christen; A. Clappier; B. Feddersen; S.-E. Gryning; G. Martucci; H. Mayer; V. Mitev; T. R. Oke; et al. (Theoretical and Applied Climatology, 2005)

Polymorphic variation of CYP1A1 is associated with the risk of gastric cardia cancer: a prospective case?cohort study of cytochrome P-450 1A1 and GST enzymes - Mark J. Roth; Christian C. Abnet; Laura Lee Johnson; Steven D. Mark; Zhi Wei Dong; Philip R. Taylor; Sanford M. Dawsey; You-Lin Qiao (Cancer Causes & Control, 2004)

Genetic structure of Mesoamerican populations of Big‐leaf mahogany ( Swietenia macrophylla ) inferred from microsatellite analysis - Rachel Roth Novick; Christopher w. Dick; Maristerra R. Lemes; Carlos Navarro; Adalgisa Caccone; Eldredge Bermingham (Molecular Ecology, 2003)
While microsatellites have been used to examine genetic structure in local populations of Neotropical trees, genetic studies based on such high‐resolution markers have not been carried out for Mesoamerica as a whole. Here we assess the genetic structure of the Mesoamerican mahogany Swietenia macrophylla King (big‐leaf mahogany), a Neotropical tree species recently listed as endangered in CITES which is commercially extinct through much of its native range. We used seven variable microsatellite loci to assess genetic diversity and population structure in eight naturally established mahogany populations from six Mesoamerican countries. Measures of genetic differentiation ( F ST and R ST ) indicated significant differences between most populations. Unrooted dendrograms based on genetic distances between populations provide evidence of strong phylogeographic structure in Mesoamerican mahogany. The two populations on the Pacific coasts of Costa Rica and Panama were genetically distant from all the others, and from one another. The remaining populations formed two clusters, one comprised of the northern populations of Mexico, Belize and Guatemala and the other containing the southern Atlantic populations of Nicaragua and Costa Rica. Significant correlation was found between geographical distance and all pairwise measures of genetic divergence, suggesting the importance of regional biogeography and isolation by distance in Mesoamerican mahogany. The results of this study demonstrate greater phylogeographic structure than has been found across Amazon basin S. macrophylla . Our findings suggest a relatively complex Mesoamerican biogeographic history and lead to the prediction that other Central American trees will show similar patterns of regional differentiation.

Magneto-encephalogram artifacts caused by electro-encephalogram electrodes - R. Murdick; B. J. Roth (Medical & Biological Engineering & Computing, 2003)

Phosphorus budget and phosphorus availability in soils under organic and conventional farming - F. Oehl; A. Oberson; H.U. Tagmann; J.M. Besson; D. Dubois; P. Mäder; H.-R. Roth; E. Frossard (Nutrient Cycling in Agroecosystems, 2002)

The Occurrence and Distribution of Selected Trace Elements in the Upper Rio Grande and Tributaries in Colorado and Northern New Mexico - H. E. Taylor; R. C. Antweiler; D. A. Roth; T. I. Brinton; D. B. Peart; D. F. Healy (Archives of Environmental Contamination and Toxicology, 2001)

Expression of liver fatty acid binding protein alters growth and differentiation of embryonic stem cells - Friedhelm Schroeder; Barbara P. Atshaves; Olga Starodub; Amy L. Boedeker; Roger R. Smith; John B. Roths; William B. Foxworth; Ann B. Kier (Molecular and Cellular Biochemistry, 2001)

Acquisition of oral phencyclidine self-administration in rhesus monkeys: effect of sex - M. E. Carroll; M. E. Roth; R. K. Voeller; P. D. Nguyen (Psychopharmacology, 2000)

Geostrophic Wind, Gradient Wind, Thermal Wind And The Vertical Wind Profile – A Sample Analysis Within A Planetary Boundary Layer Over Arctic Sea-Ice - R. Roth; M. Hofmann; C. Wode (Boundary-Layer Meteorology, 1999)

Dopamine D 4 receptor antagonist reversal of subchronic phencyclidine-induced object retrieval/detour deficits in monkeys - J. D. Jentsch; Jane R. Taylor; D. Eugene Redmond Jr; John D. Elsworth; Kenneth D. Youngren; Robert H. Roth (Psychopharmacology, 1999)

Efferent synaptic connections of dopaminergic neurons grafted into the caudate nucleus of experimentally induced parkinsonian monkeys are different from those of control animals - C. Leranth; John R. Sladek Jr.; Robert H. Roth; D. Eugene Redmond Jr. (Experimental Brain Research, 1998)

Aerodynamic Roughness of Urban Areas Derived from Wind Observations - C.S.B. Grimmond; T. S. King; M. Roth; T. R. Oke (Boundary-Layer Meteorology, 1998)

Prefrontal cortical involvement in phencyclidine-induced activation of the mesolimbic dopamine system: behavioral and neurochemical evidence - J. David Jentsch; A. Tran; Jane R. Taylor; Robert H. Roth (Psychopharmacology, 1998)

A comparison of estimated and calculated effective porosity - Daniel B. Stephens; Kuo-Chin Hsu; Mark A. Prieksat; Mark D. Ankeny; Neil Blandford; Tracy L. Roth; James A. Kelsey; Julia R. Whitworth (Hydrogeology Journal, 1998)

Maryland Biological Stream Survey: Development of a Fish Index of Biotic Integrity - N. Roth; M. Southerland; J. Chaillou; R. Klauda; P. Kazyak; S. Stranko; S. Weisberg; L. Hall; R. Morgan II (Environmental Monitoring and Assessment, 1998)

Preliminary Studies on the Population Genetics of the Central Stoneroller (Campostoma anomalum) from the Great Miami River Basin, Ohio - R. N. Silbiger; S. A. Christ; A. C. Leonard; M. Garg; D. L. Lattier; S. Dawes; P. Dimsoski; F. McCormick; T. Wessendarp; D. A. Gordon; A.C. Roth; M. K. Smith; et al. (Environmental Monitoring and Assessment, 1998)

Maryland Biological Stream Survey: A State Agency Program to Assess the Impact of Anthropogenic Stresses on Stream Habitat Quality and Biota - R. Klauda; P. Kazyak; S. Stranko; M. Southerland; N. Roth; J. Chaillou (Environmental Monitoring and Assessment, 1998)

The Effects of Acid Precipitation and Ozone on the Ectomycorrhizae of Red Spruce Saplings - Diana R. Roth; Timothy J. Fahey (Water, Air, & Soil Pollution, 1998)

TRP64ARG β3-adrenergic receptor and obesity in Mexican Americans - K. Silver; Braxton D. Mitchell; Jeremy Walston; J. D. Sorkin; Michael P. Stern; Jesse Roth; A. R. Shuldiner (Human Genetics, 1997)

Trisomy associated with loss of maturation capacity in a long-term embryogenic culture of Abies alba - R. Roth; I. Ebert; J. Schmidt (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Behavioral ecology ofMyiopharus doryphorae (riley) andM. aberrans (townsend), tachinid parasitoids of the colorado potato beetle - E. R. López; L. C. Roth; D. N. Ferro; D. Hosmer; A. Mafra-Neto (Journal of Insect Behavior, 1997)

Distribution of the [3H]-label from low doses of radioactive ochratoxin a ingested by rats, and evidence for DNA single-strand breaks caused in liver and kidneys - Amadou Kane; Edmond Eku Creppy; Angelika Roth; Robert Rschenthaler; Guy Dirheimer (Archives of Toxicology, 1986)

Propagation of Aleutian disease parvovirus in cell line CCC clone 81 - Sabine van Dawen; O. -R. Kaaden; Susanne Roth (Archives of Virology, 1983)

Timing applications for control of potato aphids on Long Island - W. A. Rawlins; R. W. Roth; J. E. Dewey (American Journal of Potato Research, 1943)